2014
DOI: 10.1021/la5039238
|View full text |Cite
|
Sign up to set email alerts
|

Successful Differentiation of Neural Stem/Progenitor Cells Cultured on Electrically Adjustable Indium Tin Oxide (ITO) Surface

Abstract: In order to control differentiation of neural cells and guide the developed neurites to targets, polyelectrolyte multilayer (PEM) films were used because of their capability of modulation of electrical charged characteristics, thickness, and stiffness. In this work, we suggested that indium tin oxide (ITO) is an alternative surface to achieve the above-mentioned objectives. A microfluidic system with four culture chambers was developed and each chamber consisted of parallel ITO surfaces for the application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…[36] In our PC12 assay results, we found that PC12 cells can adhere on all three surfaces, PLL/ CNTs@PDA, PDA, and PLL surfaces (Figure 8), which is in accord with the previous references. [30,36] It is also observed that the PLL/CNTs@PDA multilayerf ilms favor the elongation of neural synapses compared with the PDA and PLL surfaces. This phenomenon was attributed to the influence of the nanotopographic structure of the PLL/CNTs@PDA multilayer films, which has been proved by other researches focusingo nt he relationship between electrospun nano-fibrous scaffolds and PC12 cell growth.…”
Section: Pc12 Cells Proliferationsupporting
confidence: 92%
See 2 more Smart Citations
“…[36] In our PC12 assay results, we found that PC12 cells can adhere on all three surfaces, PLL/ CNTs@PDA, PDA, and PLL surfaces (Figure 8), which is in accord with the previous references. [30,36] It is also observed that the PLL/CNTs@PDA multilayerf ilms favor the elongation of neural synapses compared with the PDA and PLL surfaces. This phenomenon was attributed to the influence of the nanotopographic structure of the PLL/CNTs@PDA multilayer films, which has been proved by other researches focusingo nt he relationship between electrospun nano-fibrous scaffolds and PC12 cell growth.…”
Section: Pc12 Cells Proliferationsupporting
confidence: 92%
“…For instance, PLL‐grafted hydrogels greatly enhance PC12 cell survival in encapsulation, proliferation, and neurite growth . One research paper indicates that PDA can also promote adhesion and differentiation of PC12 cells . In our PC12 assay results, we found that PC12 cells can adhere on all three surfaces, PLL/CNTs@PDA, PDA, and PLL surfaces (Figure ), which is in accord with the previous references .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Meanwhile, electrical stimulation mediates the stem cell adhesion, migration or differentiation behaviors. 12 For potential use in nerve tissue engineering, NPCs was selected to verify the biocompatibility of composite electrode in vitro. NPCs cultured on the substrates aer 5 days were stained with Calcein-AM and EthD-1, respectively.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…9,10 Among these systems, the electro-responsive system is emerging to present a controlled release prole that mimics physiological processes in electroactive tissues owing to its intriguing properties of the versatility on the design of electrical stimulation devices or DDSs, 11 as well as the controllability through the tunable magnitude of voltage, frequency and pulse time. Besides, it has been reported that mild electrical stimulation facilitated the promotion of cell proliferation or differentiation, 12 providing the potential of electro-responsive DDSs in tissue engineering.…”
Section: Introductionmentioning
confidence: 99%